# Find the Slope and Y-Intercept 3(y-2)+6(x+1)-2=0?

**Solution:**

3 (y - 2) + 6 (x + 1) - 2 = 0

By further calculation

3y - 6 + 6x + 6 - 2 = 0

6x + 3y - 2 = 0

First we should find the slope

The equation should be rewritten in y = mx + c form

3y = - 6x + 2

Divide the equation by 3

y = - 2x + 2/3

Slope = - 2

We should substitute x = 0 to find the y-intercept

y = - 2x + 2/3

y = - 2 (0) + 2/3

y = 2/3

Therefore, the slope is -2 and y-intercept is 2/3.

## Find the Slope and Y-Intercept 3(y-2)+6(x+1)-2=0?

**Summary:**

The slope and y-intercept of 3 (y - 2) + 6 (x + 1) - 2 = 0 is -2 and 2/3.